Kualitas Pelayanan, Disiplin, Dan Fasilitas Terhadap Kepuasan Masyaraka Di Kelurahan Kenayan Kecamatan Tulungagung Kabupaten Tulungagung - Yuwanta, M. Fahriza Habib; Mega Hastuti, Sri Haryuni (Universitas Islam Kadiri, 2025)
The rapid progress in society and the dynamic relationship between society and government as well as the existence of government bureaucracy, requires government officials who work at the micro level (where direct service by officials to the community takes place) or those who place themselves at the forefront to be clear. This study aims: (1) To analyze the influence of service quality individually on community satisfaction. (2) To analyze the influence of discipline individually on community satisfaction. (3) To analyze the influence of facilities individually on community satisfaction. (4) To analyze the influence of service quality, discipline, and facilities simultaneously on community satisfaction. (5) To analyze which of the service quality, discipline, and facilities has the dominant influence on community satisfaction. This study uses a quantitative analysis method, namely analysis of data that has been scored according to a predetermined measurement scale using statistical formulas. The analysis used is data in the form of numbers. While the quality test uses (1) Descriptive statistical analysis, (2) Verification analysis. (3) Classical assumption test (4) Multiple regression analysis, and (5) Hypothesis testing, (6) Determination Coefficient Analysis (R2). The results of the study indicate that: (1) Service quality partially has a significant effect on public satisfaction. (2) Discipline partially has a significant effect on public satisfaction. (3) Facilities partially have a significant effect on public satisfaction. (4) Service quality, discipline, and facilities simultaneously have a significant effect on public satisfaction. (5) Among the factors that include service quality, discipline, and facilities, the ones that have the greatest effect on the level of change in public satisfaction are the discipline variable followed by service quality, and finally the facilities variable.